OBJECT-ORIENTED MATHEMATICAL MODEL OF SPATIAL VIBRATIONS OF RAIL VEHICLES - Myamlin, S. V.; Pshinko, O. M.; Pysmennyi, Ye. O.; Prykhodko, V. I. (Science and Transport Progress, 2005)
In article the technique of drawing up of the differential equations of fluctuation of rail crew that has allowed to define principles of «automatic» construction of these equations is in detail considered. Classes which contain the functions which are carrying out all necessary operations above objects and communications, their connecting from which the model of crew can be constructed are described.